PENGARUH PENERAPAN TEKNOLOGI INFORMASI TERHADAP EFISIENSI PELAKSANAAN TUGAS TENAGA ADMINISTRASI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Resthi Fatchinnafis; Rika Kusdinar; Shofwan Hendryawan (LPPM UNSAP, 2026)
This research aims to determine the implementation of information technology and the efficiency of task execution by administrative staff, to identify the relationship between information technology implementation and task efficiency, and to measure the extent of the influence of information technology implementation on task efficiency of administrative staff at the Population and Civil Registration Office of Sumedang Regency. This study uses a descriptive analysis method with a quantitative approach. The type of statistics used is descriptive statistics with a non-probability sampling technique, specifically saturated sampling. The sample consisted of 65 respondents. The analysis includes percentage calculation, normality test, correlation coefficient test, significance test, and determination coefficient test. Based on the results, the implementation of information technology at the Population and Civil Registration Office of Sumedang Regency is categorized as good, with an analysis score of 83.8%. The task efficiency of administrative staff also falls under a very good category, with a score of 83%. The correlation test results show a value of 0.909, indicating a very strong relationship between information technology implementation and task efficiency. The significance test resulted in a t-value greater than the t-table (17.283 ≥ 1.998). The coefficient of determination test yielded a value of 0.826, meaning that 82.6% of the variation in task efficiency can be explained by the implementation of information technology, while the remaining 17.4% is influenced by other factors not discussed in this study.